Who can organize and exercise effective resistance? A southern criminology perspective on the victimology of state crime - Vegh Weis, Valeria (Theoretical criminology, 2023)
More than 75 million people were killed in wars, dictatorships and civil conflicts in the 20th century alone. To date, states and international organizations have been regarded as the reliable entities for addressing these atrocities. However, these agencies are often perpetrators (or bystanders) that even deny their crimes. Based on a southern criminology approach, the article examines whether challenging atrocities becomes more feasible if organizations led by the victim-survivors themselves take precedence over established state-based or international entities. The key hypothesis is that the degree of effective resistance is directly related to the degree of victims’ involvement in the process. Moreover, this article will go beyond the state of the art (based on victim participation) by advocating a victim-driven model, where victims’ networks play a leading role that is independent from the state and international organizations.